Time-Dependent Negative Effects of Verbal and Non-verbal Suggestions in Surgical Patients—A Study on Arm Muscle Strength - Zech, Nina; Schrödinger, Matthias; Seemann, Milena; Zeman, Florian; Seyfried, Timo F.; Hansen, Ernil (Frontiers in Psychology, 2020)
Introduction: The medical environment is full of suggestions that affect patients and their healing. Most of them inadvertently are negative, thus evoking nocebo effects. Recently, we have reported on the effect of such verbal and nonverbal suggestions as well as alternative formulations on maximal muscular arm strength in healthy volunteers. In the present study we tested the same suggestions in patients at two time points to evaluate nocebo effects in a clinical situation and the impact of the approaching surgery date. Methods: In 45 patients, maximal muscular strength during arm abduction was measured by dynamometry of the deltoid muscle group. One test was several days before, and the second on the evening before surgery. Baseline values were compared to the performance after exposure to 18 verbal and nonverbal suggestions. The sequence of presumably negative and positive suggestions was randomized for each patient in order to avoid cumulation effects of immediate succession of two negatives. State anxiety was evaluated at both time points, and suggestibility was measured after surgery. Results: Strong and statistically significant weakening effects were observed with all presumed negative suggestions from daily clinical practice including words of encouragement (91.4% of baseline), evaluation of symptoms (89.0%), announcement of a medical intervention (82.8%), a negative memory (86.5%), expectation of an uncertain future (82.8%), and nonverbal signals (87.7-92.2%). In contrast, alternative formulations did not interfere with muscular performance in most cases. A more pronounced effect reactions was observed in the test repeated closer to the date of surgery, accompanied by a 15% higher anxiety level. The increase in anxiety correlated slightly with stronger weakening effects of suggestions, as did suggestibility. Conclusions: Negative suggestions cause a decrease in arm muscle strength, i.e. a “weakening” of the patient. This effect is enhanced by an increase in anxiety as the time of treatment, like surgery, approaches. The reaction can be avoided by alternative formulations. These nocebo effects objectively measured and quantified by a decrease in arm muscle strength are more pronounced in patients, i.e. in a clinical situation, than in healthy volunteers.